Bacteriostasis of Escherichia coli by milk. I. Colonization of breast-fed infants by milk resistant organisms. - Dolby, J. M. (Cambridge University Press, 1977)
Human milk has a bacteriostatic effect on Escherichia coli in vitro. The milks of 40 mothers were tested for this effect against E. coli isolated from their stools, from those of their own babies, and from those of babies not breast-fed. The milks had a direct bacteriostatic effect, not dependent on complement, on some but not all the strains of E. coli. Breast-fed babies receiving supplementary bottle feeds were colonized with milk-resistant strains, whereas bottle-fed babies and, surprisingly, babies completely breast-fed were colonized equally with milk-sensitive and milk-resistant strains, as were the mothers. These results suggest that the bacteriostatic effect of human milk, demonstrable in vitro does sometimes operate in vivo. The antibacterial activity of human milk is not infleunced by the O, H, or K antigens of E. coli and is effective against other Gram-negative organisms, e.g. Salmonella, Klebsiella, Proteus.